Fatigue performance of RC beams strengthened with self-prestressed iron-based shape memory alloys. (1st August 2018) - Rojob, Hothifa; El-Hacha, Raafat
Highlights: Iron-based shape memory alloys bars were used in strengthening RC beams. The beams were exposed to 6 million fatigue cycles at a frequency of 3 Hz. Strengthening with Fe-SMA enhanced the flexural performance at service conditions. Fatigue loading caused continuous deterioration of bond between Fe-SMA and concrete. The Fe-SMA bar ruptured after 5.5 million cycles near the anchor. Abstract: The behavior of RC beams strengthened with self-prestressed NSM Iron-Based Shape Memory Alloy (Fe-SMA) bars under fatigue loading is experimentally investigated. Four beams divided into two sets are tested; the first set of beams is exposed to 6 million cycles of fatigue loading at different loading limits, while no fatigue loading is applied to the second set. Each set contains one control beam and one strengthened beam. The results of the first static load cycle indicates that strengthening with NSM Fe-SMA bars significantly improves the performance of the RC beams under service load conditions. During fatigue loading, the beam strengthened with NSM Fe-SMA performs much better than the control beam at relatively low levels of fatigue loading (when the upper and lower limit of the fatigue loading induces 0.29 fy and 0.53 fy stress in the tension steel of the control beam, respectively). The stiffness degradation of the strengthened beam stabilizes after two million loading cycles. However, higher load limits cause continued degradation in the bond between the Fe-SMA bar and the grouting material. This degradation causes higher stress levels at the anchors, which consequently provokes the rupture of the Fe-SMA bar at the anchors' location after 5.5 million loading cycles.